PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN BUMN DI KOTA BANDUNG DENGAN ORGANIZATIONAL CITIZENSHIP BEHAVIOUR SEBAGAI VARIABEL MODERASI (Studi PT. Kimia Farma (Persero) Tbk dan PT. Bio Farma (Persero) - Dewi, Nunik Lestari; Gunawan, Yuliana; Vira, Selma Aghnia (Sosio-Didaktika: Social Science Education Journal, 2018)
This study aims to determine the effect of Transformational Leadership on Employee Performance of BUMN in Bandung City with Organizational Citizenship Behavior as a Moderation Variable. Researchers want to demonstrate the ability of moderating variables (Organizational Citizenship Behavior) that can strengthen or weaken the independent variable causal relationship (transformational leadership) to the dependent variable (performance of BUMN employees). Data was taken from two state-owned companies in the city of Bandung, namely PT. Kimia Farma (Persero) Tbk and PT. Bio Farma (Persero) because these two SOEs received BPEA awards in 2017 with the Good Performance category. Data collection techniques using questionnaires. Data analysis method used in this research is Moderated Regression Analysis (MRA). The results showed that there was an effect of transformational leadership on the performance of BUMN employees in Bandung City by 5.9%. There is also the influence of transformational leadership and Organizational Citizenship Behavior on the performance of BUMN employees in Bandung City by 37.7%. In addition there is an influence of transformational leadership on the performance of BUMN employees in Bandung City with Organizational Citizenship Behavior as a moderating variable of 37.8%, this shows that with the existence of Organizational Citizenship Behavior as a moderating variable, the influence of transformational leadership on the performance of BUMN employees in the City of Bandung to increase from 5.9% to 37.8% increasing by 31.9%.Keywords: Transformational Leadership, Organizational Citizenship Behavior, BUMN Employee Performance.